Binding actions and emotions in the infant's brain. (3rd July 2020) - Addabbo, Margaret; Turati, Chiara
ABSTRACT: The first year represents an exceptional time of development during which important social skills emerge, like action and emotion understanding. However, to date, no study explored the neural underpinnings of infants' ability to bind emotion- to action-related information. To assess this issue, we measured EEG activity while 6-month-old infants observed the same action performed by an actress displaying three different emotional expressions (happiness, anger and neutral). Results have shown that actions embedded in an emotional context (happiness and anger) elicited larger early negativity at parieto-occipital sites compared to a neutral context. This finding suggests that already at 6 months of age, infants use information coming from facial expressions to detect the saliency and relevance of others' actions.